2010
DOI: 10.1016/j.ijid.2010.02.561
|View full text |Cite
|
Sign up to set email alerts
|

The role of viruses in the aetiology of IRA in Peruvian children

Abstract: Abstracts e423 test kits). Socio demographic data was obtained using a study questionnaire.Results: Out of 536 admissions, 187 (34.9%) had acute diarrheal disease and 148 stools tested for rotavirus. Of the 148 specimens tested, 111 (75.0%) were positive for rotavirus antigen and 37 (25.0%) were negative. Ninety (81.1%) of the positive cases, were aged 12 months and below. There was no significant difference in the age specific prevalence rates (c2 = 0.50, p = 0.48).The mode of feeding, and other identifiable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…IPC can reduce the risk of TB transmission even in settings with limited resources [ 6 ]. A study, published elsewhere, on the potential to transmit TB at our hospital confirmed the high incidence of TB and a substantial risk for transmission [ 7 ]. This situation intensifies the need for a comprehensive hospital-based IPC programme to prevent the transmission of TB.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…IPC can reduce the risk of TB transmission even in settings with limited resources [ 6 ]. A study, published elsewhere, on the potential to transmit TB at our hospital confirmed the high incidence of TB and a substantial risk for transmission [ 7 ]. This situation intensifies the need for a comprehensive hospital-based IPC programme to prevent the transmission of TB.…”
Section: Introductionsupporting
confidence: 57%
“…The major influences were inadequacies associated with the healthcare system. Routine IPC audits at different departments of our hospital had showed inconsistently applied transmission-based precautions, even where known TB cases were admitted on a routine basis [ 7 ]. Effective TB-IPC practices by nurses were hampered by the lack of clear TB policy directives, the lack of appropriate isolation facilities and availability of PPE, the lack of TB training for staff and patients, and a persistent work overload.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, findings from this study also indicated that HCWs who worked in other areas of the hospital including non-clinical areas, such as the stores department, also had a greater incidence of TB. This suggests that TB transmission may be occurring throughout hospitals due to patients suspected of TB placed in general medical wards or patients unsuspected of TB being hospitalized for extended periods of time [ 23 , 24 ]. These findings indicate a need to urgently investigate infection control measures and practices throughout hospitals including non-clinical areas and ensure all hospital staff members receive infection control training.…”
Section: Discussionmentioning
confidence: 99%